2018
DOI: 10.2505/4/jcst18_047_04_83
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Understanding and Perceptions of Assigned Team Roles in a Classroom Laboratory Environment

Abstract: Using a cooperative learning framework in a quantitative reasoning laboratory course, students were assigned to static teams of four in which they adopted roles that rotated regularly. The roles included: team leader, protocol manager, data recorder, and researcher. Using a mixed-methods approach, we investigated students' perceptions of the team roles and specifically addressed students' understanding of the roles, students' beliefs in their ability to enact the roles, and whether working with assigned team r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The lesson is observed to be more organized as each learner has own learning responsibilities. This findings support past studies who confirmed by assigning roles in the structure of a collaborative learning will help foster interdependence in a team, maintaining order and ensuring everyone involved (Gangel, 2016;Johnson & Johnson, 2018;Ott, Kephart, Stolle-McAllister, & LaCourse, 2018).…”
Section: Assigning Learners' Rolessupporting
confidence: 89%
“…The lesson is observed to be more organized as each learner has own learning responsibilities. This findings support past studies who confirmed by assigning roles in the structure of a collaborative learning will help foster interdependence in a team, maintaining order and ensuring everyone involved (Gangel, 2016;Johnson & Johnson, 2018;Ott, Kephart, Stolle-McAllister, & LaCourse, 2018).…”
Section: Assigning Learners' Rolessupporting
confidence: 89%
“…For cooperative learning, students struggled in their groups with what to do in their assigned roles, and team roles did not help them complete the laboratory task efficiently and promptly. Instead, it deterred their progress because they were confused and wasted a lot of time determining what every member was supposed to do (Ott et al, 2018). Whelan et al (2015) highlighted the lack of appropriate instructions and feedback from instructors.…”
Section: Anxieties and Challenges In The Science Laboratory Learning ...mentioning
confidence: 99%
“…They enjoyed doing the high-level inquiry experiments more than the low-level inquiry (Henige, 2011) and said that the pre-laboratory modules helped them more than did laboratory manuals in understanding the concepts (Moozeh et al, 2019). Ott et al (2018) reported that for the cooperative learning groups, students indicated their highest preference for the role of the data recorder among rotationally assigned roles. Besides they found strength from their peers since they did not feel confident performing the tasks alone.…”
Section: Students' Preferences In Laboratory Instructionmentioning
confidence: 99%
“…The working environment in traditional laboratories was either working individually or in pairs. However, institutions are under immense pressure for considering increase in capacity of laboratory classes and experiences, associated with the benefits involving students (Ott et al, 2018). There is lack of evidence about how students perceive team roles and promote team interdependence in a learning environment, despite of increased usage of team roles within a cooperative environment.…”
Section: Introductionmentioning
confidence: 99%
“…There is lack of evidence about how students perceive team roles and promote team interdependence in a learning environment, despite of increased usage of team roles within a cooperative environment. Specific roles are needed to be assigned to the students for developing positive interdependence and provide students with increased exposure to various roles enacting by the scientists (Ott et al, 2018). Role models in education are ethical leaders who are symbols of special achievement and offer outstanding services (Allen, 2000).…”
Section: Introductionmentioning
confidence: 99%